Pemanfaatan Media Lingkungan dalam Pembelajaran PAI di SMKN 3 Kota Bima - Yaqin, Nurul; Ruslan, Ruslan; Ilham, Ilham (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
This study intends to analyze the technique and the impact of using environmental media in PAI learning at SMKN 3 Kota Bima, as well as using a descriptive qualitative research type. The data collection techniques used are interview, documentation, and observation techniques. The results of the study reveal that there are two techniques used in utilizing environmental media, namely: first; field practice carried out in the form of utilizing the mosque as a place for worship and aqidah education and the use of the school yard as a place for fostering Al-Qur'an reading. Second; integration of PAI material with the natural environment and social environment. Thus, the two techniques have an impact on increasing motivation, understanding and student learning outcomes as well as creating a sense of love and care for students for the environment. The obstacles in the use of environmental media, namely the existence of some students who are less responsive in understanding learning material due to the lack of knowledge and ability of a small number of teachers in utilizing environmental media as well as internal problems that come from students.